2018
DOI: 10.1002/jcla.22435
|View full text |Cite
|
Sign up to set email alerts
|

Significant association between RGS14 rs12654812 and nephrolithiasis risk among Guangxi population in China

Abstract: Our results suggest that the RGS14 polymorphism is involved in the etiology of nephrolithiasis and thus may be a genetic marker for nephrolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…We determined the effects of identified human genetic variants within the PDZ motif of RGS14 on NHERF1 binding, and found that one (Asp 563 Asn) disrupted the RGS14:NHERF1 complex and blocked RGS14 actions. RGS14 is implicated by numerous GWAS studies to be involved in various forms of chronic kidney diseases (14)(15)(16)(17)(18)(19). Relevant to that, we identified here at least one human genetic variant that blocks RGS14 actions on PTH-sensitive phosphate uptake.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We determined the effects of identified human genetic variants within the PDZ motif of RGS14 on NHERF1 binding, and found that one (Asp 563 Asn) disrupted the RGS14:NHERF1 complex and blocked RGS14 actions. RGS14 is implicated by numerous GWAS studies to be involved in various forms of chronic kidney diseases (14)(15)(16)(17)(18)(19). Relevant to that, we identified here at least one human genetic variant that blocks RGS14 actions on PTH-sensitive phosphate uptake.…”
Section: Discussionsupporting
confidence: 57%
“…The RGS14 PDZ ligand is present throughout the primate order and in sheep. RGS14 has been implicated by numerous GWAS studies in various forms of chronic human kidney diseases (14)(15)(16)(17)(18)(19). Relevant to that, we identify here one human genetic variant (D563N) that disrupts RGS14 binding to NHERF1 and its capacity to inhibit PTH-sensitive phosphate uptake.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Recent genomewide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) within the RGS14 gene locus associated with kidney dysfunction [33][34][35]. Subjects with genetic polymorphisms within and outside the RGS14 gene locus have higher susceptibility to nephrolithiasis [34][35][36][37][38], reduced glomerular filtration rates [33], and elevated levels of serum phosphate [39], all of which are indicative of kidney dysfunction [40]. Additionally, SNPs within the RGS14 gene are associated with elevated levels of parathyroid hormone (PTH) [41] and fibroblast growth factor 23 (FGF23) [42], which are both critical for proper kidney function [43].…”
Section: Rgs14 Protein Tissue Distributionmentioning
confidence: 99%
“…Association of rs12654812 with nephrolithiasis was validated in a Japanese population 36 . However, studies in Chinese population were not totally consistence with each other 37,38 . RGS14 encodes a member of the regulators of G-protein.…”
Section: Discussionmentioning
confidence: 99%